Basic Life Support Measures Training among High School Students: an Untapped Workforce - Baweja, Himanshi; Sharma, Sarit; Sharma, Shruti; Kashyap, Heema (Indian Journal of Community Health, 2024)
Background: In the wake of recent increasing incidences of out of hospital cardiac arrest (OHCA) even in younger population, training of high school students in basic life support (BLS) or cardiopulmonary resuscitation (CPR) measures could help save lives and improve outcomes. So, current study was planned to assess the knowledge and attitude about BLS measures among high school students. Methodology: From the four selected schools of Ludhiana district, 400 students of 9th and 10th class were included in the study after approval from school administration. A preformed questionnaire was introduced to the students followed by an interaction on concept of BLS by the investigators. The data was analysed using percentages, proportion and Chi square test for qualitative variables. A p-value of less than 0.05 was considered as statistically significant. Results: Out of 400 students, only 128 (31.75%) had heard about BLS/CPR and 30.2% of students had seen someone performing BLS/CPR. Nearly 83% of students did not have any formal training on BLS and 81% felt that their knowledge regarding BLS was insufficient. Approximately 77% students were willing to perform CPR after receiving training and 81% suggested that it should be made part of school curriculum. Higher number of students in the age group of 16-18 years felt the need of BLS training as compared to that in 13-15 years (83.7% vs. 77.6%) and were willing to perform CPR after being trained (82.9% vs. 74.7%). Conclusions: Current knowledge in high school students about BLS is low, yet if given appropriate training, these students have the potential to save lives and moreover, students are willing to learn. So, BLS training should be made part of school curriculum as students are already in the learning phase of their lives and this will immensely benefit the community.